EFFECT OF PRODUCTS, PROMOTION, AND DISTRIBUTION OF PURCHASING DECISIONS ON FIGHTING BRAND - Slamet Heri Winarno; Nurvi Oktiani (Universitas Bina Sarana Informatika, 2020)
The presence of the fighting brand is the company's strategy to capture market share. In addition to releasing superior products that already exist in the market, it is also important for companies to fill the niche of business that is still empty, one of which is by introducing the fighting brand. Soft drinking products are currently favored by various groups of old, young, and children. This research is intended to determine the significant influence of marketing factors consisting of products, promotions, and distribution on the purchasing decision of S-tee soft drink brand fighter products produced by PT. Sinar Sosro. The study used respondents who have a habit of consuming S-tee products as many as 320 people. The data analysis method uses path analysis statistical techniques, which analyze the effect of each of the variables studied. Partially, promotion and distribution variables have a significant influence on purchasing decisions. The results also showed that 41.7% of the purchasing decisions of S-tee fighter brand products were influenced by product, promotion, and distribution, while 58.3% were influenced by other factors.